2007
DOI: 10.1074/jbc.m611501200
|View full text |Cite
|
Sign up to set email alerts
|

The Major Secreted Cathepsin L1 Protease of the Liver Fluke, Fasciola hepatica

Abstract: A protease secreted by the parasitic helminth Fasciola hepatica, a 37-kDa procathepsin L1 (FheproCL1), autocatalytically processes and activates to its mature enzyme (FheCL1) over a wide pH range of 7.3 to 4.0, although activation is more rapid at low pH. Maturation initiates with cleavages of a small proportion of molecules within the central region of the prosegment, possibly by intramolecular events. However, activation to fully mature enzymes is achieved by a precise intermolecular cleavage at a Leu ؊12 -S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…However, our data indicate that FheCL1 is resistant to this proteolytic degradation, which is consistent with our earlier findings showing that the mature enzyme is highly resistant to proteolytic degradation by endopeptidases (33). We have also shown that FheCL1 can degrade cystatins/serpins such as SCCA1 and SCCA2 (34) and therefore this may protect the enzyme from inhibition by cystatins within the lysosome that are known to regulate the activity of resident endolysosomal cathepsins (35).…”
Section: Discussionsupporting
confidence: 81%
“…However, our data indicate that FheCL1 is resistant to this proteolytic degradation, which is consistent with our earlier findings showing that the mature enzyme is highly resistant to proteolytic degradation by endopeptidases (33). We have also shown that FheCL1 can degrade cystatins/serpins such as SCCA1 and SCCA2 (34) and therefore this may protect the enzyme from inhibition by cystatins within the lysosome that are known to regulate the activity of resident endolysosomal cathepsins (35).…”
Section: Discussionsupporting
confidence: 81%
“…1 B ). To determine whether the native zymogen packaged within EVs could undergo pH-dependent autocatalytic activation similar to our purified recombinant cathepsin Ls ( 35 37 ), soluble extracts of the 15 K vesicle pellet were incubated at low pH (pH 4.5) for up to 3 h at 37 °C. Western blot analysis of the in vitro auto-activation process shows that the 37 kDa zymogen diminishes over time, concomitant with the appearance of a band corresponding to the processed 24 kDa mature enzyme ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The initial event might be performed by the same protease or a different protease, such as asparaginyl endopeptidase or cathepsin B or L. Our data showing that recombinant Ov -CF-1 did not undergo autocatalytic activation, despite displaying low-level activity, suggested that native Ov -CF-1 requires trans -processing. Stack and co-workers described how the junction between the prosegment and mature enzyme of human and helminth cysteine proteases consists of a non-conserved, randomly-structured motif that is susceptible to cleavage at several sites, depending on the processing enzyme [24]. Based on the three-dimensional structure of human cathepsin F [50] and multiple sequence alignments with helminth orthologues (Figure 1), we predict that the protease-susceptible region of Ov -CF-1 prosegment is the peptide PTPQEDVTMD.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction products were analyzed by 4–12% Bis-Tris NuPage gel (Invitrogen) electrophoresis. Trans -processing of recombinant Ov -CF-1 was undertaken by mixing 50 µg purified recombinant enzyme with 5.0 µg of recombinant O. viverrini asparaginyl endopeptidase [17] or an activated recombinant Fasciola hepatica cathepsin L (FhCL1) [24] in 0.1 M sodium acetate, pH 4.5, 1 mM DTT , 1.25 mM EDTA in a total reaction volume of 150 µl. The mixture was incubated for 180 min at 37°C, and samples (10 µl) were removed at intervals for analysis (as above).…”
Section: Methodsmentioning
confidence: 99%